Measurement of labour taxation - Jan Tecl (European Financial and Accounting Journal, 2018)
Measurement of taxation of individuals is currently an interesting topic, as there is a number of people who can perform their job from any place in the world and their net income is one of the most important criteria on the basis of which their final decision is being made. Level of labour taxation is also important for international companies, which consider the location of their business and one of their important criteria is labour taxation. Provided the companies want to pay their employees equal net wage in each country, high labour taxation increases their costs. This also means that the labour taxation is related to the country's competitiveness. However, there is not just one way of measurement of labour taxation, because one can distinguish between nominal, average, effective and marginal tax rates on labour and there is also the tax wedge which could measure the labour taxation. The aim of this paper is to re-calculate numbers for the implicit tax rate (tax wedge) on labour in the EU countries for the newer period based on the Eurostat data according to the Mendoza et al. (1994) and Wolff (2005) methodology. These values will be in turn compared with data on the tax wedge measured by the Eurostat using their own methodology. One could expect that each methodology could give slightly different results, but these results should be similar. If there are differences between these values, the decision of individuals could be incorrectly affected by different values of labour taxation.
Keywords: H24; 650; Eurostat; Implicit tax rate; Labour taxation